Respon Masyarakat Terhadap Pelaksanaan Reses Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Di Kecamatan Wolio Kota Baubau - Rahim, Roslina; Tenri, Andi (Jurnal Sosiologi Miabhari, 2025)
This article examines the dynamics of public response to the implementation of legislative recess activities conducted by members of the Regional House of Representatives (DPRD) in Wolio District, Baubau City, through the lens of social psychology. The study focuses on three interrelated aspects: citizens perceptions of the legislators motives for attending recess sessions, their attitudes toward the implementation of these sessions, and the forms of participation that emerge throughout the process. Employing a descriptive qualitative method, data were collected through in-depth interviews with residents, community leaders, and local administrative figures. The findings reveal that positive perceptions of DPRD members, particularly those who engage in open and direct communication, contribute significantly to the development of proactive attitudes and increased civic participation. Public attitudes are shaped by their evaluation of the usefulness of the recess, the quality of the communication process, and the extent to which their aspirations are acknowledged and addressed. Nevertheless, citizen participation remains limited in the early stages of planning, such as community-level deliberations, which are often perceived as exclusive and not fully accessible. Trust in the recess process is largely constructed through lived experience, social influence, and a sustained sense of political involvement. Recess sessions that lack concrete follow-up actions tend to provoke feelings of apathy among constituents. Therefore, the presence of DPRD members must be accompanied by a substantive commitment to listen actively and respond meaningfully to public concerns. This study underscores the critical importance of fostering social trust as a foundational element for meaningful political participation at the local level.